Cell viscosity influences haematogenous dissemination and metastatic extravasation of tumour cells - Gensbittel, Valentin; Yesilata, Zeynep; Bochler, Louis; Follain, Gautier; Nemoz-Billet, Laurie; Lefebvre, Olivier; Uhlmann, Klemens; Larnicol, Annabel; Ammirati, Giulia E.M.; Harlepp, Sébastien; Goswami, Ruchi; Girardo, Salvatore; et al. (Nature Materials, 2026)
Metastases arise from a multistep process during which tumour cells face several microenvironmental mechanical challenges, which influence metastatic success. However, how circulating tumour cells (CTCs) adapt their mechanics to such microenvironments is not fully understood. Here we report that the deformability of CTCs affects their haematogenous dissemination and identify mechanical phenotypes that favour metastatic extravasation. Combining intravital microscopy with CTC-mimicking elastic beads, mechanical tuning in tumour lines and profiling of tumour-patient-derived cells, we demonstrate that the inherent mechanical properties of circulating objects dictate their ability to enter constraining vessels. We identify cellular viscosity as a rheostat of CTC circulation and arrest, and show that cellular viscosity is crucial for efficient extravasation. Moreover, we find that mechanical properties that favour extravasation and subsequent metastatic outgrowth can be opposite. Altogether, our results establish CTC viscosity as a key biomechanical parameter that shapes several steps of metastasis.
CRIS-Team Scopus Importer:2026-01-30